2012
DOI: 10.18433/j3w896
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Ischemia-Reperfusion Increases Efflux for Uric Acid Via Paracellular Route in the Intestine, but Decreases that Via Transcellular Route Mediated by BCRP

Abstract: -Purpose. Uric acid is thought to be one of the most important antioxidants in human biological fluids. Intestinal ischemia-reperfusion (I/R) is an important factor associated with high rates of morbidity and mortality. Reactive oxygen species (ROS) are responsible for intestinal I/R injury. The aim of this study was to clarify the efflux for uric acid from the intestine after intestinal I/R. Methods. We used intestinal ischemia-reperfusion (I/R) model rats. Serosal to mucosal flux for [14 C]-uric acid was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…Unlike ABC transporters, however, BCRP has only one N-terminal ATP-binding domain [28,29,30]. Reduced intestinal excretion of UA is often associated with polymorphisms of the BCRP gene [26] or with a lack of BCRP dimerization, which is due to oxidative stress [31,32]. …”
Section: Purine Metabolism and Uric Acid Physiologymentioning
confidence: 99%
“…Unlike ABC transporters, however, BCRP has only one N-terminal ATP-binding domain [28,29,30]. Reduced intestinal excretion of UA is often associated with polymorphisms of the BCRP gene [26] or with a lack of BCRP dimerization, which is due to oxidative stress [31,32]. …”
Section: Purine Metabolism and Uric Acid Physiologymentioning
confidence: 99%
“…9,10) On the other hand, we have recently reported that the paracellular route is the major urate transport pathway across the blood-placental barrier. 11) Urate paracellular movement was also observed in avian renal proximal tubules 12) and in the rat intestine. 13) However, the detailed mechanisms for paracellular urate transport remain elusive.…”
Section: Introductionmentioning
confidence: 86%
“…The rats were housed for at least 1 day (190-350 g in body weight). The housing conditions were the same as those described previously (Ogura et al, 2012). During the period of acclimatization, the rats were allowed free access to food and water.…”
Section: Animalsmentioning
confidence: 99%